Thirteenth General Review of Quotas : Assessing the Adequacy of IMF Resources. (Policy Papers; Policy Paper ;, 2007)
The Thirteenth Review provides an opportunity to take stock of the overall adequacy of IMF resources in light of developments in the world economy and the international monetary system. The Resolution concluding the Twelfth Review indicated that the Executive Board intended, during the period of the Thirteenth Review, to monitor closely and assess the adequacy of Fund resources and to consider measures to achieve a distribution of quotas that reflects developments in the world economy and to strengthen the governance of the Fund. The latter two issues have since been taken up under the work program on quota and voice reform. Accordingly, the focus of this paper is on the adequacy of Fund resources.